What determines international and inter-sectoral knowledge flows? The impact of absorptive capacity, technological distance and spillovers - Florian Seliger (ETH Zurich, KOF Swiss Economic Institute, 2016)
This paper studies determinants of knowledge flows as measured with patent forward citations that occur between 'input' and 'output sector-countries'. We look at the impact of absorptive capacity of a focal sector-country, knowledge spillovers and technological distance between sector-countries on further knowledge flows. For this purpose, we develop a knowledge flow matrix similar to input-output tables in trade where patent citations capture knowledge flows that go from the input sector-country to the output sector-country. We estimate a gravity model with variables that capture technological distance and knowledge that comes from either inside the input output pair or from external spillover sources. Our results indicate that knowledge accumulated in the output sector-country and - in some cases - external spillovers are key in generating further knowledge flows that go to the output sector-country. A distinction between high-tech and low-tech sector-countries shows that spillovers are more useful for the generation of knowledge flows if the input sector-country is low-tech. Low-tech sector-countries benefit from both high-tech knowledge from the output sector-country and external knowledge from the technological frontier. In contrast, knowledge flows based on high-tech sector-countries cannot benefit from low-tech sector-countries and only to a very limited extent from other high-tech sources. Technological distance between sector-countries has a negative impact on further knowledge flows so that only technologically proximate sector-countries are more likely to generate knowledge flows.
Keywords: O33; 330; Knowledge flows; Patent citations; Spillovers; Absorptive capacity; Gravity model